Reading ESEF Filings with Arelle: Opportunities and Problems - Zvekan, Goran (Eurasian Business and Economics Perspectives. EBES 2023., 2024)
The European Single Electronic Format (ESEF) introduced mandatory reporting in eXtensible Business Reporting Language (XBRL) in 2020. XBRL is more advantageous compared to data from commercial databases that only use standard financial statements. The data is more granular and non-standardized which avoids errors in data collection. While financial reports are available in XBRL format, it is rather unclear how to process them. Academic research is extracting XBRL elements with self-created software code, which requires significant programming knowledge. Additionally, the methods of XBRL data extraction are rarely specified in detail. In this paper, an open-source software called Arelle is introduced as a tool to process and analyse ESEF filings in XBRL format. Arelle is a certified XBRL software that enables the processing of XBRL filings without any prior knowledge of programming and allows the transfer into common formats such as CSV. Opportunities via Arelle, such as XBRL elements extraction or the checking of validation errors for XBRL assurance are presented by analysing German DAX 40 filings. Issues include reporting errors such as the use of incorrectly implemented prefixes. Therefore, this work is an introduction to an XBRL processing software that lacks user guides as well as its opportunities and limitations for user
Keywords: Audit software; ESEF; Financial reporting; XBRL